Strategi dalam Mewujudkan Keharmonisan Rumah Tangga bagi Istri yang Ditinggal Suami Merantau di Jorong Balai Gurah Kanagarian Balai Gurah Kecamatan Ampek Angkek - Rhesti Maulana; Beni Firdaus (Lembaga Yasin AlSys, 2026)
The phenomenon of many husbands migrating for work to earn a living in Jorong Balai Gurah creates particular challenges for wives in maintaining household harmony and integrity. This study aims to examine the strategies used by wives to maintain household integrity while their husbands are away for work and to review them from the perspective of Islamic law. This study employed a qualitative approach with a descriptive design. The main informants of the study were five wives whose husbands had migrated for work. Data were collected through observation, interviews, and documentation and were then analyzed descriptively and qualitatively. The results showed that the main strategies used by the wives included open communication, mutual trust, the performance of dual roles in the household, and efforts to maintain mental and physical health. Emotional support from husbands through video calls and involvement in decision-making also played a role in maintaining household harmony. From the perspective of Islamic law, migrating for work is permissible as long as certain conditions are fulfilled, such as the wife’s permission, regular provision of maintenance, and maintained communication. If these conditions are not fulfilled, the wife has the right to file for divorce. The conclusion of this study affirms that the strategies implemented by the wives are in line with the principles of Islamic law in maintaining a family characterized by sakinah, mawaddah, and rahmah. These findings contribute to studies of Muslim families, particularly regarding household resilience in the context of husbands migrating for work, and provide practical implications for couples in building communication, trust, and family responsibility on an ongoing basis.